Moth smoke - Mohsin, hamid (New Delhi Penguin group, 2000)
It follows the story of Daru Shezad, a disillusioned former banker who finds himself grappling with poverty and the fallout of his privileged past after losing his job. As he descends into a life of desperation and drug use, he becomes entangled in a love triangle with his former best friend$1 (Bs wife, Muna.s
Keywords: English- Book